Exploring Tadulako University Students’ Perceptions Toward the Use of ChatGPT Voice as an English Speaking Practice Tool - Ismi Awalia; Darmawan Darmawan; Wahyudin Wahyudin (Hasanuddin University, 2026)
Speaking skill is an essential competence in English language learning; however, it remains a challenge for many students, particularly in terms of fluency, confidence, and limited opportunities for real-life practice. With the advancement of digital technology, ChatGPT Voice has emerged as an alternative learning medium that allows students to practice speaking in a more flexible and accessible way. This study aims to explore the perceptions of students from the English Education Department of Tadulako University toward the use of ChatGPT Voice as an English speaking practice tool. This research employs a qualitative approach with narrative analysis, involving students selected through snowball sampling. Data were collected through semi-structured interviews and analyzed by identifying patterns of experiences and meanings constructed by the participants. The findings reveal that students’ perceptions of ChatGPT Voice are generally positive, as the tool provides a comfortable and low-pressure learning environment that encourages active speaking practice, reduces anxiety, increases confidence, and supports linguistic development such as fluency, vocabulary, and pronunciation through repeated interaction and feedback. However, students also recognize several limitations, particularly the lack of authentic human interaction, including emotional expression and natural conversational dynamics. Therefore, ChatGPT Voice is not perceived as a replacement for real communication, but rather as a supplementary tool that is used independently, selectively, and strategically in developing students’ speaking skills.